2017
DOI: 10.1007/978-3-319-67744-6_28
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Want Your Chatbot? An Exploratory Wizard-of-Oz Study with Young, Urban Indians

Abstract: As text-messaging chatbots become increasingly "human", it will be important to understand the personal interactions that users are seeking with a chatbot. What chatbot personalities are most compelling to young, urban users in India? To explore this question, we first conducted exploratory Wizard-of-Oz (WoZ) studies with 14 users that simulated interactions with a hypothetical chatbot. We evaluated three personalities for the chatbot-Maya, a productivity oriented bot with nerd wit; Ada, a fun, flirtatious bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 28 publications
4
44
0
1
Order By: Relevance
“…Nguyen (2019) also tried to examine whether a chatbot could improve the consumer experience when the chatbot possesses the capability of understanding. Research also has shown that chatbot agents that understand and use humans' humor are ranked more likable, cooperative, and capable as well as provide better solutions and performance than those that do not understand it (Sensuse et al 2019;Thies et al 2017). The dimension of understandability in this study is distinct from the information understandability (or ease of understanding) as one of the information quality dimensions proposed by Lee et al (2002) or Wang and Strong (1996).…”
Section: Chatbot Quality Dimensionsmentioning
confidence: 66%
“…Nguyen (2019) also tried to examine whether a chatbot could improve the consumer experience when the chatbot possesses the capability of understanding. Research also has shown that chatbot agents that understand and use humans' humor are ranked more likable, cooperative, and capable as well as provide better solutions and performance than those that do not understand it (Sensuse et al 2019;Thies et al 2017). The dimension of understandability in this study is distinct from the information understandability (or ease of understanding) as one of the information quality dimensions proposed by Lee et al (2002) or Wang and Strong (1996).…”
Section: Chatbot Quality Dimensionsmentioning
confidence: 66%
“…Studies on the alleviation of negative effects of CA response failures, have examined how politeness and apologetic behavior on the part of the CA alleviates users' emotional reactions after a response failure (Lee et al, 2010;Medhi Thies et al, 2017). Other scholars have explored repair strategies to facilitate the completion of tasks left unfinished because of response failures, such as offering alternative answer options or further explanations (Ashktorab et al, 2019;Følstad & Taylor, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It does not imply that innovation for development should be sidelined. The issues pertaining to accessibility and aging (e.g., [8]), healthcare (e.g., [13,27]), information literacy, sustainability (e.g., [9,22]) will continue to pose challenges, increasingly from the perspective of new and emerging technologies (e.g., [15])]. However, they need to be looked as part of the larger social, cultural and political contexts.…”
Section: Including and Beyond Developmentmentioning
confidence: 99%